2019
DOI: 10.1111/dom.13745
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors and cancer: A meta‐analysis of randomized controlled trials

Abstract: Aim: The aim of this meta-analysis of randomized trials was to assess the effects of SGLT-2i on the overall incidence of malignancies and on different types of cancer, summerizing the results of trials with a duration of at least 1 year. This was done in light of the effect of SGLT-2 inhibitors (SGLT-2is) that has been highlighted by some studies, showing an increased incidence of bladder cancer, particularly with use of empagliflozin.Materials and methods: A Medline and Embase search for "Canaglifozin", "Dapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 34 publications
4
46
1
Order By: Relevance
“…In a meta‐analysis of clinical trials, SGLT2is were associated with an increased risk of bladder cancer 7 . Although this was not confirmed in the most recently published meta‐analysis, it has to be considered that high‐risk patients for bladder cancer (those with a history of previous bladder cancer, radiation to lower abdomen or pelvis or unexplained hematuria) were excluded 8 . Although our results of reporting disproportionality cannot be compared with the results of the meta‐analyses, we can suggest the possible association of SGLT2is with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta‐analysis of clinical trials, SGLT2is were associated with an increased risk of bladder cancer 7 . Although this was not confirmed in the most recently published meta‐analysis, it has to be considered that high‐risk patients for bladder cancer (those with a history of previous bladder cancer, radiation to lower abdomen or pelvis or unexplained hematuria) were excluded 8 . Although our results of reporting disproportionality cannot be compared with the results of the meta‐analyses, we can suggest the possible association of SGLT2is with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Later, a meta‐analysis of clinical trials suggested that the administration of an SGLT2i, especially empagliflozin, was associated with a higher risk of bladder cancer compared to placebo or other glucose‐lowering treatments 7 . Nevertheless, a more recent meta‐analysis including only studies with >52 week follow‐up concluded that available data from randomized trials do not suggest a detrimental effect of SGLT2is on the incidence of malignancies in general, or in bladder cancer in particular 8 . However, as this trial excluded patients at high risk for bladder cancer, the potential association between SGLT2is and bladder cancer remains unclear.…”
mentioning
confidence: 99%
“…Inhibition of the SGLT2 transporter leads to increased urinary excretion of glucose, resulting in a decline in plasma glucose concentrations. A recent meta‐analysis of 27 RCTs concluded that current evidence does not indicate an association of SGLT2 inhibitors with an increased risk of bladder or any other cancer . Further, a meta‐analysis of seven studies on dapagliflozin found no association with cancer risk .…”
Section: Types Of Antidiabetes Medicationmentioning
confidence: 99%
“…The newest class of oral diabetes drugs, the sodium glucose transporter-2 inhibitors (SGLT2-I) (empagliflozin, dapagliflozin, canagliflozin, and ertugliflozin), reduces plasma glucose by inhibiting renal glucose reabsorption and increasing urinary glucose excretion. These drugs are not only not linked to an increased risk of malignancies [59,60], but preclinical studies also indicated, mainly for canagliflozin, an interesting anti-proliferative effect on liver cancer cells [61][62][63][64][65]. SGLT2-I are potentially useful to treat diabetes in cancer patients, although the increased risk of genitourinary infections, volume depletion, and euglycaemic diabetic ketoacidosis should be carefully considered.…”
Section: Sodium Glucose Transporter-2 Inhibitorsmentioning
confidence: 99%